2008
DOI: 10.1021/ja807799k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Active Site Residues of GDP-Fucose Synthase

Abstract: L-fucose, 6-deoxy-L-galactose, is a key component of many important glycoconjugates including the blood group antigens and the Lewis(X) ligands. The biosynthesis of GDP-L-fucose begins with the action of a dehydratase that converts GDP-D-mannose into GDP-4-keto-6-deoxy-mannose. The enzyme GDP-fucose synthase, GFS, (also known as GDP-4-keto-6-deoxy-D-mannose epimerase/reductase, GMER) then converts GDP-4-keto-6-deoxy-D-mannose into GDP-L-fucose. The GFS reaction involves epimerizations at both C-3'' and C-5'' f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Mass spectrometry analysis of reaction products generated in the presence of deuterium was necessary to resolve the issue. Such experiments have been used previously to characterize the C3/C5 epimerization activities of similar enzymes (30,50,51). Our experiments on deuterated reaction compounds clearly demonstrated that Cjj1430 only has C3 epimerization activity on the heptose substrate, which leads to the 4-keto-D-arabino sugar intermediate P4 (Fig.…”
Section: Paradox In the Gdp-6-deoxy-d-altro-heptose Biosynthesis Pathsupporting
confidence: 53%
See 1 more Smart Citation
“…Mass spectrometry analysis of reaction products generated in the presence of deuterium was necessary to resolve the issue. Such experiments have been used previously to characterize the C3/C5 epimerization activities of similar enzymes (30,50,51). Our experiments on deuterated reaction compounds clearly demonstrated that Cjj1430 only has C3 epimerization activity on the heptose substrate, which leads to the 4-keto-D-arabino sugar intermediate P4 (Fig.…”
Section: Paradox In the Gdp-6-deoxy-d-altro-heptose Biosynthesis Pathsupporting
confidence: 53%
“…Significance of Elucidation of This Pathway-Although C3/C5 epimerases and C3/C5 epimerases/C4 reductases that function on deoxy-hexoses, have attracted much attention for their potential use as antibacterial targets (30,33,34,50,51), no such enzyme involved in heptose modification pathways has been characterized at the biochemical level to date. These enzymes also represent novel antibacterial targets because they are likely involved in the modification of the heptoses found in virulence-associated surface carbohydrates of a variety of pathogens, including several strains of C. jejuni (19,21,22), Campylobacter lari (52), as well as Burkholderia species (53).…”
Section: Paradox In the Gdp-6-deoxy-d-altro-heptose Biosynthesis Pathmentioning
confidence: 99%
“…The enzymes studied are unique as they use heptose-based substrates, whereas all other C3/C5 epimerases and C3/C5 epimerases/C4 reductases studied to date use hexose-based substrates (2,6,7,14,34). Also the ring configuration and the nucleotide portion of the substrates used by these enzymes differ widely compared with the substrates of previously studied enzymes.…”
Section: Heptose-modifying Enzymes As New Glycobiology Tools-mentioning
confidence: 99%
“…For example, GFS, GMER, and GME use the epimerization substrate GDP-6-deoxy-4-keto-D-lyxo-mannose that is closely related to the GDP-6-deoxy-4-keto-D-lyxo-heptose used by MlghB and DdahB in this study. However, these enzymes differ from MlghB and DdahB in that they all have additional C4 reductase activity, and GME even generates its own 4-keto from GDP-mannose via additional C4 oxidase activity (6,7,14). Sequence-wise, MlghB and DdahB are less related to these GFS, GMER, and GME enzymes, although they use related substrates, than to the RmlC and RfbC enzymes that only have C3/C5 epimerase activities like MlghB and DdahB but use a very different substrate: dTDP-6-deoxy-Dxylo-4-hexulose (ϭdTDP-4-keto-6-deoxy-glucose) (2,34).…”
Section: Heptose-modifying Enzymes As New Glycobiology Tools-mentioning
confidence: 99%
See 1 more Smart Citation